2010
DOI: 10.2135/cropsci2009.06.0311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs Associated with Partial Resistance to White Mold in Soybean Using Field‐Based Inoculation

Abstract: White mold caused by Sclerotinia sclerotiorum (Lib.) de Bary can be an important cause of yield loss in soybean. Only partial resistance to this disease has been found to date, and little is known about the loci contributing to this resistance. The objectives of this study were to identify quantitative trait loci (QTL) associated with partial resistance to white mold progression on the main stem. One hundred eighty F4–derived lines from a cross between a partially resistant cultivar, Maple Donovan, and a susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 47 publications
1
34
0
6
Order By: Relevance
“…In soybean, bi-parental linkage mapping led to the discovery of many quantitative trait loci (QTL) for resistance to this pathogen. Remarkably, a total of 103 QTL on 18 of the 20 soybean chromosomes have been recorded in SoyBase (Grant et al, 2009) with minimal overlap between QTL reported by different studies (Arahana et al, 2001;Huynh et al, 2010;Kim and Diers, 2000;McCaghey et al, 2017;Moellers et al, 2017;Wei et al, 2017). Despite these efforts, gene level and mechanistic details of soybean resistance mechanisms against S. sclerotiorum remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In soybean, bi-parental linkage mapping led to the discovery of many quantitative trait loci (QTL) for resistance to this pathogen. Remarkably, a total of 103 QTL on 18 of the 20 soybean chromosomes have been recorded in SoyBase (Grant et al, 2009) with minimal overlap between QTL reported by different studies (Arahana et al, 2001;Huynh et al, 2010;Kim and Diers, 2000;McCaghey et al, 2017;Moellers et al, 2017;Wei et al, 2017). Despite these efforts, gene level and mechanistic details of soybean resistance mechanisms against S. sclerotiorum remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The previous mapping studies have identified a total of 103 QTLs (http:// www.soybase.org/), which distributed on 17 chromosomes (LGs) of soya bean. Among these QTLs, only six loci were identified under field conditions (Huynh et al, 2010;Kim and Diers, 2000) and the rest were identified under greenhouse or growth chamber studies with various artificial inoculation methods (Arahana et al, 2001;Guo et al, 2008;Vuong et al, 2008). Unfortunately, these tests under controlled conditions produced a poor correlation with the resistance observed in the field (Guo et al, 2008;Nelson et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to biotic stresses Angular leaf spot QTL 22-64 Oblessuc et al, 2012;Teixeira et al, 2005 (Khedikar et al, 2010;Liang et al, 2009a;Qin et al, 2012;Sujay et al, 2012;Wang et al, 2013 (Gautami et al, 2012b;Ravi et al, 2011;Varshney et al, 2009b) Gautami et al, 2012a;Liang et al, 2009;Ravi et al, 2011;Selvaraj et al, 2009;Shirasawa et al, 2012;Varshney et al, 2009b) (Continued on next page) (Liang et al, 2009;Pandey et al, 2012c;Sarvamangala et al, 2011;Selvaraj et al, 2009;Shirasawa et al, 2012) Pea Plant height QTL 19-65 (Tullu et al, 2008;Tar'an et al, 2003b;Dirlewanger et al, 1994) (Atibalentja et al, 2005;Guo et al, 2006;Guo et al, 2008;Han et al, 2008;Huynh et al, 2010;Kazi et al, 2008;Ruben et al, 2006;Shi et al, 2008;Silva and Danielle, 2008;Vuong et al, 2008;Wang et al, 2010;Winter et al, 2007) (Continued on next page) Funatsuki et al, 2005;Githiri et al, 2006;Githiri et al, 2007;…”
Section: Common Beanmentioning
confidence: 99%